Out of darkness [videorecording (DVD)] - Cumming, Andrew (Director); Greenberg, Ruth (Ruth Helen); Kassman, Oliver, 1988-; Oakley-Green, Safia, 2001-; Young, Kit, 1994-; Modu, Chuku, 1990-; Evans, Iola , 2002-; Lüning, Arno, 1963-; Mwezi, Luna, 2007- (Decal, 2024)
45,000 years ago, six people searched for a new home in an inhospitable landscape. When night falls, hope turns to fear as they realize they are not alone. Stalked by a terrifying enemy, the group fractures as everyone fights for survival.